Octupole vibrations in even–even isotopes of Dy / A.A. Okhunov, G.I. Turaeva and M. Jahangir Alam - Okhunov, A.A.; Turaeva, G.I.; Alam, M. Jahangir (2015)
The phenomenological model is used for the study of the characteristics of low – lying states of negative parity in Dy. The spectra of octupole bands and reduced probability of E1– transitions are discussed. Calculated level energies and B(E1) values are compared with experimental data. Within this phenomenological model firstly introduced for actinides, it is possible to obtain good results for rare earth region as well.